Case Report: Triple Negative Ulcerated Breast Cancer with Immunosuppressive Cold Tumor Environment - Iin Asriani; Andy Visi Kartika; M. Akram Chalid (PSPP JOURNALS, 2026)
Breast cancer is the most common malignancy among women worldwide according to Global Cancer Observatory (GLOBOCAN) data. One aggressive clinical form is ulcerative breast cancer, which is often categorized as locally advanced breast cancer (LABC). We report a case of a 42-year-old woman presenting with a left breast mass for 7 months that progressively developed into an ulcer with brownish, tea-colored discharge, without pain in the early phase and without systemic symptoms. Physical examination revealed an ulcerative mass with irregular margins, granulation tissue, and superficial collateral veins. Histopathological findings from FNAB and incisional biopsy confirmed invasive breast carcinoma of no special type (NST), WHO grade 3, with lymphovascular space invasion (LVSI+). Radiological evaluation showed no distant metastasis. The absence of pain and systemic inflammation in this case may be associated with the predominance of immunosuppressive cytokines such as IL-10 and TGF-β, which suppress nociceptor activation and systemic inflammatory responses, despite ongoing local inflammation. Management was carried out using a multimodal approach including supportive therapy, antibiotics, and planned mastectomy as definitive treatment. This case highlights the importance of clinical vigilance, as ulcerative breast cancer may progress without significant systemic symptoms.